MATHEMATICS PROBLEM SOLVING THROUGH MAKE A DRAWING STRATEGY FOR ELEMENTARY SCHOOL STUDENTS WITH MILD INTELLECTUAL DISABILITY - Suryaningsih, Tri; Arita Marini,; Linda Zakiah, (AULADUNA: Jurnal Pendidikan Dasar Islam, 2024)
Abstract Mild intellectual disability are children who have below-average IQ. This study aims to describe the ability of a student with mild intellectual disability to solve mathematics problems using the make-a-drawing strategy. The method used in this research was qualitative research. The subject was a student with special needs who was in grade IV but had a grade-1 level of ability. The data collection process was carried out using an interview and a test. The data validity test conducted in this study involved the triangulation technique. The qualitative data analysis stage consisted of four steps: data collection, data reduction, data presentation, and the last stage involved drawing conclusions and verification. The results showed that the make-a-drawing strategy could facilitate mild intellectual disability students to develop mathematical problem-solving skills, strengthen their understanding of concepts, and increase their confidence in dealing with various daily mathematical situations.